Geological characteristics of the Daduhe gold belt, western Sichuan, China: Implications for exploration - Zhang Yize; Chen Zailin; Zhang Chengjiang; Ni Shijun; Cheng Xianfeng; Kexin Liu (Open Geosciences)
Geological characteristics, genetic model, and exploration implications in the Daduhe gold belt are studied. Three categories of gold deposits have been distinguished: “gold deposits in the basement (GDB),” “gold deposits in the cover layer (GDC),” and “gold deposits at the interface (GDI).” Among them, quartz vein type and quartz vein altered rock type are the main types of mineral deposits. The following features have been obtained: (1) inclusions of gold particles exist in pyrite, pyrrhotite, quartz, sellaite, and other sulfides; in fractures; or along cracks and grain margins. (2) The distribution curve of rare earth elements in pyrite and quartz indicates strong mineralization intensity in the GDB, (La/Sm)N fractionation characteristics, suggesting that pyrite may be more influenced by crustal materials and quartz by mantle materials. (3) The H–O and He–Ar isotopes manifested the ore-forming fluids derived from the mixing between crust and mantle. (4) The ranges of δ 34 S values of pyrite (−5.0 to 7.6‰) are consistent with those of metasomatized mantle lithosphere. (5) The homogenization temperatures and salinity of all quartz inclusions are concentrated from 150 to 210°C and 2.1–8.7 wt%, indicating a medium-low-temperature, low-salinity hydrothermal fluid. (6) The Daduhe orogenic gold deposits can be defined as epizonal subtypes. (7) The Daduhe gold deposits are medium-low temperature, low-salinity, and epizonal orogenic gold deposits, and fluid comes from a mixture of crust and mantle. In the future, efforts should be made to increase the exploration of deep gold deposits.